1984
DOI: 10.1111/j.1365-2125.1984.tb02472.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of a pharmacokinetic interaction between nifedipine and the beta‐ adrenoceptor blockers metoprolol and atenolol.

Abstract: Nifedipine, metoprolol and atenolol were administered orally to young, healthy volunteers. Each drug was given alone and nifedipine was also given with both beta‐adrenoceptor blockers. Each drug was given for 3 days immediately before the study days. Plasma and urine drug concentrations were measured and the relevant pharmacokinetic parameters calculated. No pharmacokinetic interaction between nifedipine and the beta‐adrenoceptor blockers was revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1986
1986
1991
1991

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…None of these differences is statistically significant. Other studies with multiple doses of nifedipine have shown a significant effect on the disposition of propranolol (but not betaxolol) (Vinceneux et al, 1986) or alternatively no significant effects on the disposition of atenolol, propranolol and metoprolol (Gangji et al, 1984;Kendall et al, 1984), although two of these latter studies again showed higher values for the Cmax of the ,B-adrenoceptor blocker. With felodipine a significant kinetic interaction has been identified with metoprolol (Kendall et al, 1984).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…None of these differences is statistically significant. Other studies with multiple doses of nifedipine have shown a significant effect on the disposition of propranolol (but not betaxolol) (Vinceneux et al, 1986) or alternatively no significant effects on the disposition of atenolol, propranolol and metoprolol (Gangji et al, 1984;Kendall et al, 1984), although two of these latter studies again showed higher values for the Cmax of the ,B-adrenoceptor blocker. With felodipine a significant kinetic interaction has been identified with metoprolol (Kendall et al, 1984).…”
Section: Discussionmentioning
confidence: 81%
“…Other studies with multiple doses of nifedipine have shown a significant effect on the disposition of propranolol (but not betaxolol) (Vinceneux et al, 1986) or alternatively no significant effects on the disposition of atenolol, propranolol and metoprolol (Gangji et al, 1984;Kendall et al, 1984), although two of these latter studies again showed higher values for the Cmax of the ,B-adrenoceptor blocker. With felodipine a significant kinetic interaction has been identified with metoprolol (Kendall et al, 1984). Thus, although not all studies have shown statistical significance, the weight of evidence suggests that there is a significant interaction between dihydropyridine calcium antagonists and ,B-adrenoceptor blockers (particularly, those which undergo hepatic metabolism) and it appears likely that the underlying mechanisms relate to changes in the extent of vasodilatation of the splanchnic, portal and hepatic circulations.…”
Section: Discussionmentioning
confidence: 81%
“…Kendall et al (1984) reported the results of concurrent nifedipine administration on the pharmacokinetics of metoprolol 100mg twice daily for 3 days in healthy volunteers: mean metoprolol Cmax, tmax, t'l2, CL and AUC(O-24) remained unchanged; however, plasma concentrations were not at steady-state when blood samples were drawn.…”
Section: ;3-adrenergic Blocking Agentsmentioning
confidence: 95%
“…In controlled single and repeated dose trials using therapeutic dosages, nifedipine produced no significant effects on the pharmacokinetics or pharmacodynamics of metoprolol, atenolol or propranolol in healthy volunteers (Elkayam et al 1986;Gangji et al 1984;Kendall et al 1984;Rosenkranz et al 1986). However, in a double-blind, crossover study with healthy volunteers receiving propranolol 80mg every 12h, the addition of nifedipine 10mg 3 times daily increased mean total propranolol Cmax by 56% (p < 0.05) compared with propranolol alone (Vinceneux et al 1986).…”
Section: ;3-adrenergic Blocking Agentsmentioning
confidence: 97%
See 1 more Smart Citation